Reflections on the Complexity of Ancient Social Heterarchies: Toward New Models of Social Self-Organization in Pre-Hispanic Colombia - Mezza-Garcia, Nathalie; Froese, Tom; Fernández, Nelson (Journal of Sociocybernetics, 2014)
All political systems have limitations in their information processing and action capacities to face large-scale crises and challenges, but especially if they happen to be too hierarchically and centrally controlled systems. In contrast, some other cultures whose political structure is heterarchically organized, such as the Zenú, the Muiscas, and the Tayronas in pre-Hispanic Colombia, presented adaptiveness even without advanced scientific knowledge and without powerful centralized top-down control. We therefore propose that creating and analyzing computer models of their decentralized processes of management could provide a broader perspective on the possibilities of self-organized political systems. Our hope is that this approach will eventually go beyond the scope of basic science. It seeks to promote more computer-model-based research of social systems that exhibit an adaptive balance of flexibility and robustness, i.e., systems that do not rely on the current ideal of rule-based control of all systemic aspects, with the practical aim of improving current social and political processes.